Islam and human rights in practice perspectives across the ummah (Routledge advances in Middle East and Islamic studies ;, 2008)
Questions over the compatibility of Islam and Human Rights have become a key area of debate in the perceived tensions between 'Islam and the West'. From conceptual discussions on the issues of gender rights and religious freedom, to examining Muslim communities from South East Asia, Central Asia, the Middle East and North Africa, leading global experts bring forth key insights into the way in which Muslim communities live and experience Human Rights. The potential for deeper engagement with this issue is critical, as it opens possibilities for more profound understanding and tolerance.